Thanatophoric dysplasia- a rare cause of stillbirth and perinatal mortality: a case report - Agrawal, Priti; Agrawal, Rishi; Lobo, Anandi (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Lethal skeletal dysplasia is estimated to occur in 0.95 per 10,000 deliveries. Thanatophoric dysplasia affects about 1in 25000 to 50000 births. The term thanatophoric is Greek word for “death bearing”. Children with this condition are usually stillborn or die shortly after birth from respiratory failure. We report a case of LSD (Thanatophoric dysplasia), in an unbooked patient where previous two children and couple were absolutely normal. Our patient, 31 years old, unbooked case presented with history of amenorrhea 8 months and unable to perceive fetal movements. Her husband’s age was 33 years. This was her third pregnancy. She had previous 2 deliveries by LSCS. Ultrasonography revealed single intrauterine live fetus in breech presentation with multiple fetal anomalies. There was shortening and deformity of all four limbs (micromelia) with poor mineralization of all bones. Thorax was pear shaped with short horizontal ribs and abnormal cardiothoracic ratio. LSCS was done in emergency for impending rupture of previous LSCS scar. Post-delivery examination and X-ray of the fetus revealed decreased skull mineralization, frontal bossing, hypoplastic nasal bone, midface hypoplasia, mandibular hypoplasia, pear shaped chest, protuberant abdomen, micromelia, dumbbell shaped appearance of all long bones. TD is caused due to mutation of the fibroblast growth factor receptor 3 gene (FGFR3), which is located on the short arm of chromosome 4. Type I TD is characterized by marked underdeveloped skeleton and short-curved long bones. Conventional radiographic examination remains the most useful means of studying the dysplastic skeleton. Bony evaluation is best done on X-rays or ultrasonography. The diagnosis of TD can be established with ultrasound and molecular confirmation in the second trimester can help in genetic counselling and termination of such lethal pregnancies. LSD’s are rare event. If our patient had undergone anomaly scan in second trimester of pregnancy, this defect could have been detected earlier. The outcome of fetus is lethal but maternal morbidity can be reduced if diagnosed early.